Narrative Theory in Journalistic Practice : Understanding Emerging Digital Genres - Yngve Benestad Hågvar; Harald Hornmoen; Jørgen Alnæs (Routledge, 2025)
Narrative Theory in Journalistic Practice provides innovative analytical frameworks for examining journalistic narratives in today's digital, multimodal media landscape. The volume expands beyond traditional models focused on linear texts to address contemporary formats across multiple platforms.Through empirical analyses of genres such as immersive long-form stories, live news reports, social media news, podcasts, and still images, the book explores the dual function of journalistic narratives: they are suited to engage readers in both trivial and complex events and issues, but will also advance certain interpretations of reality and downplay others. The book conveys a critical and constructivist view on narratives, showing how journalistic stories contribute to shaping people's understanding of reality but also how media users play an active role in interpreting the narratives.The volume will interest students and scholars of journalism, media studies, and narrative studies. It is intended for use by graduate students as well as by established researchers.